Formen der ländlichen Abwanderung in der Türkei - Struck, Ernst (ERDKUNDE, 1985)
Rural out-migration was studied by fieldwork in the area of today’s maximum out-migration in the transition area from inner Anatolia to eastern Anatolia. The development of rural out-migration can be characterized by four migration-types: (i) exploration migration (until 1950), (ii) seasonal-migration (until 1960), (iii) mass-migration (1960 till today), (iv) marriage-migration (1975 till today). After the explorational phase all further migration was induced by family ties and communication flows between the migrants and the village households. The out-migration was always prepared by the former migrants, who provided jobs and dwellings for those who followed. These strong linkages are reflected in marriage migration, which means an important intensification of mass migration. Women get married to former villagers who now live in the cities. Target-migration (Direktwanderung) was distinguished from step-wise migration (Etappenwanderung) by the decision making procedure of the migrant household. The homogeneous migration behaviour after the first phase of exploration-migration is the basis for the concept of interrelation-migration (Beziehungswanderung). Interrelation-migration is one reason for the low participation in step-wise migration and the growing female out-migration rates.